2020
DOI: 10.1038/s41586-020-2705-y
|View full text |Cite
|
Sign up to set email alerts
|

Bending the curve of terrestrial biodiversity needs an integrated strategy

Abstract: Bending the curve of terrestrial biodiversity needs an integrated strategy Summary paragraph Increased efforts are required to prevent further losses of terrestrial biodiversity and the ecosystem services it provides 1,2. Ambitious targets have been proposed, such as reversing the declining trends in biodiversity 3-yet, just feeding the growing human population will make this a challenge 4. We use an ensemble of land-use and biodiversity models to assess whether (and if so, how) humanity can reverse terrestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
438
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 612 publications
(509 citation statements)
references
References 65 publications
9
438
1
6
Order By: Relevance
“…Increasing synergies between the LCA and the biodiversity conservation communities is essential to best inform the post 2020 biodiversity targets and policies, which also mention the mainstreaming of biodiversity impacts into production processes (CBD 2020; EC 2020a). The IPBES Global Assessment has clearly indicated that societies need transformative change to address biodiversity loss and ecosystem degradation (IPBES 2019), including the way we produce and consume, if we aim to bend the curve of biodiversity loss (Marques et al 2019;Leclère et al 2020). In fact, the European Biodiversity Strategy for 2030 (European Commission 2020) states that "biodiversity considerations need to be better integrated into public and business decision making at all levels".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing synergies between the LCA and the biodiversity conservation communities is essential to best inform the post 2020 biodiversity targets and policies, which also mention the mainstreaming of biodiversity impacts into production processes (CBD 2020; EC 2020a). The IPBES Global Assessment has clearly indicated that societies need transformative change to address biodiversity loss and ecosystem degradation (IPBES 2019), including the way we produce and consume, if we aim to bend the curve of biodiversity loss (Marques et al 2019;Leclère et al 2020). In fact, the European Biodiversity Strategy for 2030 (European Commission 2020) states that "biodiversity considerations need to be better integrated into public and business decision making at all levels".…”
Section: Resultsmentioning
confidence: 99%
“…The mean species abundance (MSA) is a metric conceptually similar to the LBII, reporting the abundance of species found in relation to a given pressure relative to its abundance found in an undisturbed situation (Schipper et al 2020). Both LBII and MSA have already been used in modeling frameworks to investigate global integrated scenarios of biodiversity change in response to different environmental pressures (Newbold et al 2016;Schipper et al 2020;Leclère et al 2020), and MSA has been coupled to LCA to measure business impacts on biodiversity (Lammerant 2018; Crenna et al 2020). Because they are based on species abundances, LBII and MSA are good candidates to account for biodiversity impacts regarding ecosystem multifunctionality.…”
Section: Adoption Of Indicators From the Biodiversity Conservation Domentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological: Mechanistic modelling of honeybee populations based on individual-, colony-and population-level processes (Becher et al, 2018) Ecological: Databases of species traits such as the 'TRY' Plant Trait Database including dispersal traits (Kattge et al, 2011) Social-ecological: Agent-based modelling of huntergatherer strategies and environmental resources/ prey species in spatially explicit environment (Janssen & Hill, 2014 Social-ecological: Use of invasive species monitoring data to disentangle human-mediated and natural dispersal processes (Horvitz et al, 2017) Demographic change Social: Parallelised agent-based modelling of human population dynamics based on key processes (Montañola-Sales et al, 2016) Social: Global demographic databases (United Nations Statistics Division, 2019) Ecological: Stochastic population modelling of emperor penguin responses to climate change (Jenouvrier et al, 2009) Ecological: Bayesian modelling to extend species demography data coverage to under-studied species (Kindsvater et al, 2018) Social-ecological: Agent-based modelling of demographic change in indigenous hunting communities and their prey species (Iwamura et al, 2014) Social-ecological: Long-term data records covering changes in social and ecological communities as, e.g., road network develops in Amazon (Klarenberg et al, 2019) Institutional & governance interventions Social: Agent-based modelling of individual and institutional activities in land system (Holzhauer et al, 2019) Global/regional databases of policies and impacts relating to, for example, environment or climate (New Climate Institute, 2019;OECD, 2019) Ecological: Multi-model framework to identify pathways and policies to reverse biodiversity loss trends (Leclère et al, 2020) Social-ecological: Economic-environmental modelling to explore effects of different policies on land use and biodiversity (Bryan et al, 2016), and network modelling of the effects of social institutions on ecological conditions, for example, of coral reefs (Barnes et al, 2019) social-ecological models and datasets suggest that they are feasible (Table 2). If this approach is successfully developed and applied, it could have a number of other benefits.…”
Section: Models Datamentioning
confidence: 99%
“…Although ecological restoration can be prohibitively expensive, careful design can triple conservation benefits while halving the costs 8,9 . These cost-benefit improvements will be necessary for meeting global conservation targets to reverse land degradation and biodiversity loss 10 .…”
Section: Introductionmentioning
confidence: 99%